The Effectiveness of Using the Modern Reminder My Therapy Application on Fe Tablet Consumption Adherence - Wulandari, Rr. Catur Leny; Jannah, Muliatul; Ludin, Putri Febriyanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Background:Pregnant women have a low level of adherence to Fe tablet consumption, due to the factor of forgetting to take medicine and side effects. One of the efforts to improve adherence is to use a reminder application-based intervention, which can improve adherence in mothers who often forget to take Fe tablets.Objective:This study aimed to determine the effectiveness of using the My Therapy Modern Reminder Application on adherence to Fe Tablet Consumption in the Bangetayu Public Health Center Working Area, Semarang City.Methods:it was quasi-experimental with one group pretest, posttest design. Sampling in this study used a purposive sampling technique with a total sample of 45 respondents and data collection using the MMAS-8 questionnaire. The analysis method used the Wilcoxon test.Results:There was a significant difference between the results of the pre-test and post-test (p = 0.00). Wilxocon test results showed the effectiveness of using my therapy modern reminder application on Fe tablet consumption adherence (p = 0.00).Conclusion:The use of my modern therapy reminder application can improve the adherence of pregnant women to consuming Fe tablets.